2021
DOI: 10.3390/cells10113200
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin in Retinal Neurodegeneration: A Potential Target in Therapeutic Approaches

Abstract: Retinal neurodegeneration affects an increasing number of people worldwide causing vision impairments and blindness, reducing quality of life, and generating a great economic challenge. Due to the complexity of the tissue, and the diversity of retinal neurodegenerative diseases in terms of etiology and clinical presentation, so far, there are no cures and only a few early pathological markers have been identified. Increasing efforts have been made to identify and potentiate endogenous protective mechanisms or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Authors reported evidence on the effect of ectopic overexpression of NGB in the retinal tissue, and, in particular, in retinal ganglion cells. High induced levels of NGB have a critical function in preserving retinal neuron loss and vision pathway under different stress conditions/retinal diseases as the main consequence of the globin ability to maintain or enhance mitochondrial functions, supporting the idea of NGB as the main target candidate for preserve or restore retinal tissue during degeneration [ 8 ].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Authors reported evidence on the effect of ectopic overexpression of NGB in the retinal tissue, and, in particular, in retinal ganglion cells. High induced levels of NGB have a critical function in preserving retinal neuron loss and vision pathway under different stress conditions/retinal diseases as the main consequence of the globin ability to maintain or enhance mitochondrial functions, supporting the idea of NGB as the main target candidate for preserve or restore retinal tissue during degeneration [ 8 ].…”
mentioning
confidence: 93%
“…They estimated a NGB concentration in the retina in the range of 100 to 200 µM, comparable to MB levels in muscle and accountable for a possible NGB function in the transport or short-term storage of oxygen [ 6 ]. The paper of Solar Fernandez and collaborators [ 8 ] provides the undercurrent knowledge on NGB distribution in retinal layers and the evidence about the connection between NGB level modulation and the functional outcome in terms of retinal neuroprotection to provide a novel therapeutic/preventive target for visual pathway degenerative disease. Authors reported evidence on the effect of ectopic overexpression of NGB in the retinal tissue, and, in particular, in retinal ganglion cells.…”
mentioning
confidence: 99%
“…Intracellular Ngb concentrations range from 100 μM in the neurons of the hypothalamus and the retinal cells to 1 μM in the other neurons [ 1 , 2 , 3 ]. Furthermore, there is an average 2-5-fold increase in NGB gene expression in response to various stress signals (e.g., hypoxia or oxidative stress) [ 4 , 5 ]. Ngb is a cytoplasmic protein, although there is evidence for Ngb localization not only in close proximity to mitochondria, but also within mitochondria [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ngb overexpression significantly protects the heart and brain from hypoxia/ischemia and oxidative stress‐associated damage, whereas decreased Ngb level causes an exacerbation of tissue damage 19 . Ngb, an endogenous neuroprotective protein, is capable of reversibly binding oxygen and protecting against various insults, including ischemia, oxidative stress, and neurodegenerative conditions 20,21 . The overexpression of Ngb can protect neurons from mitochondrial dysfunction and neurodegenerative diseases such as Alzheimer's disease 19 .…”
Section: Introductionmentioning
confidence: 99%
“…19 Ngb, an endogenous neuroprotective protein, is capable of reversibly binding oxygen and protecting against various insults, including ischemia, oxidative stress, and neurodegenerative conditions. 20,21 The overexpression of Ngb can protect neurons from mitochondrial dysfunction and neurodegenerative diseases such as Alzheimer's disease. 19 Specifically, serum Ngb is related to cerebral metabolism and functional outcomes in aneurysmal arachnoid hemorrhage.…”
mentioning
confidence: 99%